Lived experiences of adults living With HIV/AIDS receiving antiretroviral therapy at werabe comprehensive specialized hospital in Silte zone, Ethiopia - Abdulmejid Mustefa; Lonsako Abute; Kemal Lemnuro; Abdulkerim Badgeba; Delwana Bedru; Bisrat Feleke Bubamo; Gizachew Beykaso; Feleke Doyore Agide; Abinet Arega Sadore (Frontiers in Reproductive Health)
BackgroundThe HIV/AIDS pandemic has had a profound impact on patients’ lives on all fronts, as well as on society. Examining adult PLWHA experiences from various angles helps find gaps, develop plans, and put policies and coping mechanisms in place. Therefore, this study aimed to explore the lived experiences of adult patients receiving ART at Werabe Comprehensive Specialized Hospital in Ethiopia.MethodA qualitative approach with a phenomenological study design was used from March to June 2022 among 12 purposively selected adults on ART at the Worabe Comprehensive Specialized Hospital. Data were collected using semi-structured, open-ended questions. In-depth interviews were audiotaped, transcribed verbatim, and analyzed using qualitative data management software (ATLAS Ti version 7.1.4). The findings were summarized under five themes by applying inductive thematic analysis.ResultsThis study explored five themes that included (I) experiences at the time of diagnosis of their positive HIV Status with two sub-themes: inappropriate counseling and difficulty in accepting positive results; (II) disease management skills with three sub-themes: ART Initiation, Perceived health importance of ART; (III) Enacted stigma with two sub-themes: Stigma & Discrimination and Disclosure; (IV) Experiences towards gaining support with three sub-themes: Family care, Peer/social support from organizations and Hospital and Health professionals’ care; and (V) perceptions towards health status and feelings about their status with three sub-themes of living as normal life, feeling about their HIV status and vision of purposeful life.ConclusionsCreating educational initiatives and consistently educating the public about health issues can greatly increase public knowledge of HIV, alter perceptions of the virus, and influence how others behave when interacting with people with HIV/AIDS. This mental shift fosters social support and lessens the obstacles to the acceptance of infection by PLWHA.